Impact of the Customer Relationship Management on the Performance of the Institutions of Microfinance in Cameroon: The Case of the CAMCCUL Network - Marie Antoinette, Simonet; David, Kamdem; Christian, Nguefack (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
The objective of this contribution is to work out the customer relationship management and the commercial performance of the institutions of microfinance (IMF) in Cameroon in order to show its impacts on the performance indicators of the latter. To achieve this goal, we have simultaneously applied the nonparametric method of the Data Envelopment Analysis (DEA) and the censored Tobit model on a sample of 60 IMF belonging to the Cameroon Cooperative Credit Union League (CAMCCUL) network. The different statistical tests carried out have first of all permitted us to estimate the IMF performance levels and then to assess the different factors which influence the commercial performance of the IMF, taking into account the indicators obtained from the literature review. As a general rule, we have realized from our results that the IMF of the CAMCCUL network are globally inefficient as regards the commercial performance, the women influence on the scores of performance being very significant, insofar as the IMF which are in majority made up of women have relatively been more impressive compared to those which are in majority made up of men. Among the factors influencing the performance, we have noted that the computerized management of the customer relationship and the proximity (closeness) of the social contacts exert a positive influence on the performance, while the satisfaction towards the past experiences with the IMF exerts a negative and very significant influence on this one.